Ha-ras Oncogene Effect on DNA Content and Chromatin Supraorganization in benzo[a]pyrene-Transformed Human Breast Epithelial Cells - Maria Luiza S. Mello; Benedicto de Campos Vidal; Jose Russo (Analytical Cellular Pathology)
When transfected to benzo[a]pyrene (BP)‐transformed MCF‐10F human breast epithelial cells (BP1 cell line) the c‐Ha‐ras oncogene has proven to enhance the neoplastic changes initiated by exposure to BP, giving rise to an aggressive tumorigenic cell line, BP1‐Tras. We have previously demonstrated by image analysis that BP affects the DNA content and the chromatin supraorganization of MCF‐10F cells. Here Feulgen‐stained BP1‐Tras cells were studied by image analysis in order to evaluate possible additional changes in DNA content and chromatin texture induced by insertion of the ras oncogene. A high variability in DNA content also including polyploidy or near‐polyploidy, and an increase in the packing states of the chromatin which became still condensed in BP1 cells were found in BP1‐Tras cells. The results differed from those reported for the BP1‐E1 cell line which is also an aggressive tumorigenic cell line, but was attained through progressive passages of BP‐transformed cells. It was demonstrated that different patterns of changes in DNA content and chromatin organization may be involved in equally aggressive tumorigenic BP‐transformed cell lines originated from the same cell line by different mechanisms.